SISTEM INFORMASI PENDATAAN PEMERLU PELAYANAN KESEJAHTERAAN SOSIAL BERBASIS WEB PADA DINAS SOSIAL KABUPATEN ENDE - Renggo, Yohanes Ratu (JURSIMA, 2022)
PPKS (Need for Social Welfare Services) is one of the social problems that exist in people's lives. Where, people or people who in their daily life because of an obstacle, are unable to carry out their social functions, so they need social services to fulfill their life needs. This research was conducted with the aim of being able to overcome problems that occur in the PPKS data collection system, and make data collection easier and more efficient. The software used in making this system is a database as a data storage medium, the programming language PHP, CSS, JavaScript, and HTML are used to create the interface. The research method used is the waterfall method and the process carried out follows the stages contained therein. Based on the above, the authors take the title "Data Collection Information System for the Need for Web-Based Social Welfare Services at the Ende District Social Service". With this data collection information system, it is hoped that it can assist in collecting data and presenting PPKS data reports. Keywords: PPKS, Information System, PHP, Database, Waterfall.